Penegakan Hukum Pidana Terhadap Pelaku Pengiklanan Judi Online Melalui Media Sosial Di Kota Tasikmalaya - Mohamad Endang (Jurnal Kedaulatan Hukum, 2025)
The development of information and communication technology (ICT) in recent decades has had a significant impact on various aspects of human life, one of which is the emergence of online gambling. The spread of online gambling advertisements through social media has become a worrying phenomenon, especially in Indonesia, where even though there are regulations governing online gambling, effective implementation of the law still faces obstacles. This study aims to analyze the effectiveness of law enforcement against online gambling advertising on social media, with a juridico-sociological approach. The results of the study indicate that the main challenges in law enforcement related to online gambling are the difficulty in identifying perpetrators, the use of fake accounts, and the limited capacity of law enforcement officers in handling technology-based cases. This study recommends increasing the capacity of officers, more massive socialization of the law to the public, and stricter supervision of social media to strengthen law enforcement and reduce the negative impacts of online gambling.